Tahrif in the Scripture: A Study of Ahmad Khan's Tabyin al-Kalam - Yusuf Rahman (Refleksi, 1999)
Muslim belief in the tahrif ("corruption") of Christian and Jewish scriptures has, from the beginning, been a major factor in Muslim polemics with Chistians and Jews. However, just as Muslims have tried to prove tahrif, the latter have tried to refute this and to assert that Muslims themselves have altered the Qur'an.